Role of special stains as a useful complementary tool in the diagnosis of renal diseases: a case series study - Venkatesh, Veenaa; Malaichamy, Vinuta (International Journal of Research in Medical Sciences, 2019)
Background: Renal diseases constitute a major cause of morbidity in clinical practice and their incidence is on rise. Investigation usually requires division into even smaller samples to permit the application of specialized techniques. Methods: This is a prospective study conducted over a period of one year from January 2018 to December 2018 in the Department of Pathology, Coimbatore. A total of 58 renal biopsies were received from the Nephrology Department and the tissues were subjected to light microscopic and special stain studies. Results: Total 53 patients (91.38%) had high blood urea nitrogen value more than 20.0 mg/dl. 48 patients (82.76%) had high serum creatinine value more than 1.2 mg/dl. Out of 58 biopsy specimens, 46 (79.31%) showed primary glomerular lesions, 10 (17.24%) showed secondary glomerular lesion and 2 (3.45%) showed tubulointerstitial nephritis. Jones’s methanamine silver stain along with PAS stain helped in typing/staging of membranous glomerulopathy and membranoproliferative glomerulonephritis. Various changes in GBM like spike formation, thickening and moth-eaten appearance of GBM was noted which is seen in MGN stage II, IV and III respectively. Double contour and thickening of GBM was noted which is seen in type I and II MPGN respectively. In Myeloma cast nephropathy, tubular casts stained negative with Congo red which was used to differentiate it from amyloid deposition. Conclusions: The special stains used in this study helped in supplementing the light microscopic findings for diagnosis of kidney lesions. However, the use of other ancillary techniques like immunofluorescence and electron microscopy would help the pathologists in better and more accurate diagnosis.